Pharmacotherapy of diabetes mellitus in patients with heart failure - a nation-wide analysis of contemporary treatment - Vicha, Marek; Skala, Tomas; Jelinek, Libor; Pavlu, Ludek; Jarkovsky, Jiri; Dusek, Ladislav; Benesova, Klara; Taborsky, Milos (Biomedical papers, 2023)
Aim. Retrospective national sub-analysis of antidiabetic pharmacotherapy in patients with diabetes mellitus (DM) and heart failure (HF) based on data reported to the National Register of Paid Health Services in the Czech Republic between 2012-2018. Methodology and Results. In 2012, there were 75,022 patients with HF and DM (i.e. 42.5% of patients with HF), 6 years later 117,265 (i.e. 41.0% of HF patients in 2018). The most represented antidiabetic drug was metformin (45.6%). Of the insulins and analogues, glargine showed the largest positive trend (5.8% 2012; 14.8% 2018). Empagliflozin was the most prescribed SGLT-2 inhibitor (1.8% in 2018). A decrease in prescribing was observed for saxagliptin (0.5% 2012; 0.1% 2018) and for sulfonylurea derivates - gliclazide (13.0% 2012; 10.3% in 2018) and glimepiride (12.9% 2012; 9.0% 2018). Linagliptin was the most prescribed dipeptidyl peptidase inhibitor (0.7% 2012; 6.8% 2018). Conclusion. In the Czech Republic, between 2012 and 2008, there was an increase in prevalence of patients with heart failure and concomitant diabetes mellitus, their proportion being similar. In correspondence with other registries, metformin was used mostly. A positive trend was observed in prescription of DDP-4 and SGLT-2 inhibitors, while there was a significant decrease in patients taking sulfonylureas.
Keywords: diabetes mellitus; heart failure; pharmacotherapy; National Register of Paid Health Services (NRHZS)